LIVE Course for free

Rated by 1 million+ students
Get app now
0 votes
16 views
in Aptitude by (30.0k points)
closed by
If x : y = 5 : 9, then which of the following is equal to (6x - 3y) : (x + 2y) ?
1. 23 : 4
2. 3 : 23
3. 23 : 3
4. 4 : 23

1 Answer

0 votes
by (54.0k points)
selected by
 
Best answer
Correct Answer - Option 2 : 3 : 23

Given:

x : y = 5 : 9

Calculation:

As, x : y = 5 : 9

Let x be 5k and y be 9k

So, (6x - 3y) : (x + 2y)

⇒ (6× 5k - 3 × 9k) : (5k + 2 × 9k)

⇒ (30k - 27k) : (5k + 18k)

⇒ 3k : 23k = 3 : 23

Hence, the value of (6x - 3y) : (x + 2y) is 3 : 23.

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

Categories

...